2017
DOI: 10.3390/met7070270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Welding Speed on Microstructure and Mechanical Property of Fiber Laser Welded Dissimilar Butt Joints between AISI316L and EH36

Abstract: Fiber laser welding of dissimilar materials between AISI316L austenitic stainless steel and EH36 ship steels were conducted. Then the effects of welding speed on microstructure and mechanical characterization of the welded joint were investigated. Optical microscopy, Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) were used to analyze the microstructure. Microhardness testing, transverse tensile strength, and impact tests at the temperature of −40 • C were performed to study the mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
0
6
0
2
Order By: Relevance
“…Haitao Wang tested and simulated the crack growth paths in a dissimilar metal welded joint and found that the crack deflected to the soft area during the experiment [28,29]. Longchao Cao [30] and Pavel Podany [31] researched the microstructure and the local mechanical properties of the dissimilar butt joints. Jianbo Li [32] studied the fracture toughness near the fusion line (HAZ and fusion line) of the dissimilar material and, in addition, found the crack deflection.…”
Section: Amendment Of Haz Fracture Toughnessmentioning
confidence: 99%
“…Haitao Wang tested and simulated the crack growth paths in a dissimilar metal welded joint and found that the crack deflected to the soft area during the experiment [28,29]. Longchao Cao [30] and Pavel Podany [31] researched the microstructure and the local mechanical properties of the dissimilar butt joints. Jianbo Li [32] studied the fracture toughness near the fusion line (HAZ and fusion line) of the dissimilar material and, in addition, found the crack deflection.…”
Section: Amendment Of Haz Fracture Toughnessmentioning
confidence: 99%
“…When the laser focal position is too large, the power density on the workpiece surface is too low to melt required levels of material. According to engineering experience and our previous researches [2,[20][21][22], the WPP are selected as follows:…”
Section: Problem Definitionmentioning
confidence: 99%
“…As intelligent manufacturing develops, accurate predicting of weld bead is becoming crucial to accomplishing industrial automation [1,2]. Therefore, it is necessary to establish the relationships between the laser keyhole welding process parameters (WPP) and weld bead geometry to predict the weld bead quality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [8] used pulsed laser welding of stainless-steel heterogeneous joints; they found that inputting a low energy pulse facilitated the production of fine grains and good mechanical properties. Cao et al [9] used laser welding of 316 L and EH36 heterogeneous joints; they found reducing the welding speed was effective in reducing the degree of tissue segregation in the joints. The laser-arc hybrid welding process couples the two heat sources with each other, fully integrating the advantages of laser and arc welding.…”
Section: Introductionmentioning
confidence: 99%